SIMBOL DALAM PUISI KETIKA MAUT MENJEMPUT KARYA JALALUDDIN RUMI - Sarah, Rima; Sakinah, R. Myrna Nur (Journal of Language and Literature, 2021)
The poem "When I Died" is one of Jalaluddin Rumi's literary masterpieces. He is known as a famous Islamic mystical Sufi until this time. Jalaludin Rumi's poem "When I Died" provides clues to humans about real death. Death here is not something scary, but a way to eternal love. This depiction of death, resurrection and immortality is a symbol found in the poem "When I Died" by Jalaluddin Rumi. Various literary works about death are often associated with sadness, grief, loss and unstoppable tears. This makes death a frightening and sad event. However, Rumi actually describes death as a step towards eternal love. This writing will show the symbolic meaning of the poem "When I Died" by using the hermeneutical analysis method from Paul Ricoeur. This method will explain the symbolic meaning of this poem and put an explanation of the symbol's meaning in real life. The result of this analysis is the discovery of various symbols contained in the poem "When I Died", including symbols of death, resurrection, and immortality.